Characteristics and susceptibility pattern of catheter-associated urinary tract infections (CAUTI) bacteria in Indonesia: A study in a national reference hospital of Sumatra region 2020–2021 - Perdana, Muhammad A.; Wahyuni, Dian D.; Yunita, Rina (Narra Sains Indonesia, 2023)
Catheter-associated urinary tract infection (CAUTI) is defined as a urinary tract infection associated with catheter placement for more than two consecutive days. Hence, antibiotic resistance in the context of CAUTIs represents a substantial challenge. The aim of this study was to present the characteristics of patients with CAUTI and the susceptibility pattern of CAUTI bacteria in the national reference hospital of the Sumatra region of Indonesia. A cross-sectional study was conducted at H. Adam Malik General Hospital, Medan, Indonesia, from 2020 to 2021, using a total sampling. All CAUTI patients included were on catheterization and diagnosed based on the Centers for Disease Control and Prevention (CDC) guidelines. The patient’s urine culture and antibiotic susceptibility test were carried out on the patient’s admitted urine sample for further assessment. Identification of bacteria, antibiotic susceptibility test, and the extended-spectrum beta-lactamase (ESBL) test for Escherichia coli and Klebsiella pneumoniae were conducted using the VITEK-2 Compact. A total of 74 CAUTI patients were included in the study, 59.5% were female, 54.1% were 46–65 years old, and a third had cardiovascular disease comorbidities (33.8%). A total of 83 CAUTI-associated bacteria were isolated. The majority were Gram-negative bacteria (74.7%), and the most bacteria isolated was E. coli (31.3%), followed by K. pneumoniae, Enterococcus faecalis, Acinetobacter baumannii, and Enterococcus faecium. The ESBL test was positive mostly in K. pneumoniae (100%) and E. coli (76.9%). CAUTI-associated E. coli was susceptible to tigecycline, meropenem, ertapenem, nitrofurantoin, and gentamicin. The isolated K. pneumoniae was susceptible to tigecycline, meropenem, ertapenem, and amikacin. While E. faecalis showed susceptibility to tigecycline, nitrofurantoin, vancomycin, imipenem, linezolid, ampicillin, piperacillin/tazobactam, amoxicillin/clavulanic acid, ampicillin/sulbactam, and piperacillin.